“Bad parents”: the social construction of parenting as a problem - Стрельник, О. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2015)
The article highlights the cognitive capabilities of socio-constructivist theory of parenting that allows creating a critical alternative to the conservative and essentialist approach in the parenthood (especially motherhood) studies.The author concludes that the discourse of the parent irresponsibility and incompetence as probably the only problem of Ukrainian families and parents is actively reproduced by Ukrainian media, academic researches and state rhetoric. Construction of parenting as the problem is not only the basis of moral panic concerning weakness of a socializing role of the modern family, but for the politicization of parenthood as well. The author notes that the discourse of parental irresponsibility covers weakness of institutional and structural conditions in which Ukrainian parents, especially mothers, care for their children.